Clinical Characteristics, Prognosis, and Gender Disparities in Young Patients With Acute Myocardial Infarction - Lv, Junxing; Ni, Lin; Liu, Kexin; Gao, Xiaojin; Yang, Jingang; Zhang, Xuan; Ye, Yunqing; Dong, Qiuting; Fu, Rui; Sun, Hui; Yan, Xinxin; Zhao, Yanyan; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Young people hold a stable or increasing percentage of patients with acute myocardial infarction (AMI) in many countries. However, data on clinical characteristics and outcomes of young AMI patients were insufficient. This study aimed to analyze clinical characteristics, prognosis and gender disparities in patients aged ≤45 years with AMI. Methods: A total of 24,125 patients from China Acute Myocardial Infarction registry were included in this study. Clinical characteristics, managements, in-hospital and 2-year outcomes were compared between patients aged ≤45 years and those aged >45 years. Predictors of all-cause death were obtained using multivariate regression models. Gender disparities of AMI were analyzed among young patients. Results: Of 24,125 patients, 2,042 (8.5%, 116 female) were aged ≤45 years. Compared with patients aged >45 years, young patients were more often male, current smokers and more likely to have medical history of hyperlipidemia. Smoking (72.1%) was major modifiable risk factor in patients aged ≤45 years. Young patients received more evidence-based medications and had significantly lower risk of both in-hospital and 2-year adverse events than older patients. Education level and left ventricular ejection fraction were independent predictors of 2-year mortality in young patients. Moreover, symptom onset to admission time of young women was significantly longer than that of young men. Young women were less likely to receive percutaneous coronary intervention, and suffered higher risk of in-hospital adverse events than young men (adjusted OR for death: 5.767, 95%CI: 1.580-21.049, P=0.0080; adjusted OR for the composite of death, re-infarction and stroke: 3.981, 95%CI: 1.150-13.784, P=0.0292). Young women who survived at discharge had a higher 2-year cumulative incidence of death (3.8% vs 1.4%, Plog-rank=0.0412). Conclusions: Patients aged ≤45 years constituted a nonnegligible proportion of AMI patients, with higher prevalence of smoking and hyperlipidemia but better care and prognosis compared with older patients. There were significant gender disparities of managements and outcomes in young patients. More efforts to improve quality of care in young women were needed.